1978
DOI: 10.1073/pnas.75.8.3826
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of myoblast phenotype by dimethyl sulfoxide.

Abstract: Application of dimethyl sulfoxide to proliferating L8 myoblasts (an established cell line of rat skeletal muscle) for 72 hr completely prevented fusion and induction of creatine phosphokinase (EC 2.7.3.2) activity (an indicator of muscle differentiation). The growth pattern changed from the usual sheets of randomly oriented cells to flattened, whorled monolayers of elongated fibroblast-like cells. By electron microscopy, rough endoplasmic reticulum increased and extracellular material appeared that had the mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…In contrast, the effects of DMSO, HMBA and NaBut were exclusively confined to an increase in creatine kinase activity used as a biochemical marker of differentiation, whereas no increase in morphological differentiation was observed and the formation of terminally differentiated postmitotic mytotube-like giant cells even significantly decreased. A corresponding inhibition of myotube formation had already been reported for non-tumorigenic myoblast cell lines after exposure to DMSO, HMBA and NaBut (Miranda et al, 1978;Blau & Epstein, 1979;Fiszman et al, 1980;Endo & Nadal-Ginard, 1987 8x 10-6± 5 x 10-6 15x 10-6+ 4x 10-6 DMSO 3.4 1.5 23 20…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In contrast, the effects of DMSO, HMBA and NaBut were exclusively confined to an increase in creatine kinase activity used as a biochemical marker of differentiation, whereas no increase in morphological differentiation was observed and the formation of terminally differentiated postmitotic mytotube-like giant cells even significantly decreased. A corresponding inhibition of myotube formation had already been reported for non-tumorigenic myoblast cell lines after exposure to DMSO, HMBA and NaBut (Miranda et al, 1978;Blau & Epstein, 1979;Fiszman et al, 1980;Endo & Nadal-Ginard, 1987 8x 10-6± 5 x 10-6 15x 10-6+ 4x 10-6 DMSO 3.4 1.5 23 20…”
Section: Discussionmentioning
confidence: 97%
“…Polar compounds such as dimethylsulphoxide (DMSO) (Friend et al, 1971;Collins et al, 1978;Tarella et al, 1982;Tsao et al, 1982), hexamethylene bisacetamide (HMBA) (Reuben et al, 1976;Ramsay et al, 1986;Mansfield et al, 1988;Snyder et al, 1988), sodium butyrate (NaBut) (Prasad & Sinha, 1976;Dexter et al, 1981;Augeron & Laboisse, 1984;Nordenberg et al, 1987;Lee et al, 1988), and N-monomethylformamide (NMF) (Dexter et al, 1982;Dibner et al, 1985;Cordeiro & Savarese, 1986;Iwakawa et al, 1987) have only been sporadically described (Dexter 1977;Garvin et al, 1986). Furthermore, DMSO, HMBA and NaBut have been reported to inhibit terminal differentiation and myotube-formation in non-tumorigenic myoblast cell lines (Miranda et al, 1978;Blau & Epstein, 1979;Fiszman et al, 1980;Endo & Nadal-Ginard, 1987). Therefore, we investigated the susceptibility of the rhabdomyosarcoma cell line BA-HAN-IC to differentiation induction with polar compounds.…”
mentioning
confidence: 99%
“…Leder and Leder [31] have also reported that DMSO and butyrate may induce by different mechanisms. Furthermore, the report that DMSO inhibits the fusion process in chick embryonic myoblasts [32] indicates that DMF, a polar solvent with chemical properties very similar to DMSO, might also be antagonistic to the myogenic process. Furthermore, the report that DMSO inhibits the fusion process in chick embryonic myoblasts [32] indicates that DMF, a polar solvent with chemical properties very similar to DMSO, might also be antagonistic to the myogenic process.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the addition of FBS in freezing medium is undoubtedly required for stable freezing of embryonic cell lines from O. dancena species. It was reported that DMSO has cytotoxic effects by inducing the alteration of membrane fluidity and cytoskeleton (Brayton 1986;Hunt 2011;Katsuda et al 1987;Miranda et al 1978).…”
Section: Discussionmentioning
confidence: 99%